Associations between Fatness, Fitness, IGF and IMT among Obese Korean Male Adolescents - Eun Sung Kim (Diabetes & Metabolism Journal, 2011)
BackgroundThe purpose of this study was to investigate the association between obesity, fitness levels and cardiovascular (CVD) risk factors, and to identify the correlation between of insulin-like growth factor (IGF)-1, IGF binding protein-3 (IGFBP-3), and carotid intima media thickness (IMT) in Korean adolescents.MethodsA total of 225 high school males with a mean age of 16.96±0.23 years participated in this study, and their fatness and fitness levels, fasting glucose, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), blood lipids, IGF-1, IGFBP-3, and IMT were measured.ResultsThe results showed that total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), fasting insulin, HOMA-IR, IGF-1, and IGFBP-3 levels were significantly higher in the most obese group than in the other two groups (tertiles). Muscular and cardiopulmonary fitness were negatively associated with weight, body mass index (BMI), fat mass, body fat, waist circumference (WC), fasting insulin, HOMA-IR, and IMT. IGF-1 and IGFBP-3 levels were correlated with WC, hip circumference (HC), fasting glucose, TG, HDL-C, fasting insulin, and HOMA-IR. IMT levels were significantly associated with weight, BMI, muscle mass, fat mass, percent body fat, WC, HC, systolic blood pressure, diastolic blood pressure and high-sensitivity C-reactive protein.ConclusionThere was a significant association between increased obesity and decreased fitness and HOMA-IR, IGF, and IMT among adolescents.